The Effectiveness of Interactive Learning Media to Improve Understanding of Fractional Summing in Elementary School Students - Arini Ulfah; Muh Syauqi Malik (STEAM Journal For Elementary School Education, 2025)
The learning problems that occurred at Bustan El Firdaus Kawunganten Islamic Elementary School, Cilacap Regency, among others, are still centered on teachers and dominated by lecture methods. This condition causes low focus of students during learning and the emergence of boredom which has an impact on low understanding, especially in the subject of Mathematics where the material sums of fractions with different denominators are used. In response to this, the researcher designed improvements through Classroom Action Research using Kahoot interactive learning media. The novelty of this research lies in the integration of competitive and interactive real-time quiz-based digital media into mathematics learning at the elementary school level, which is still rarely applied systematically in the local context. The research was conducted in two cycles, each consisting of two meetings lasting two hours of lessons. The data collection technique uses quantitative instruments in the form of individual tests given at the end of each cycle. The average grade point of the class in the pre-cycle was 68 with a completion rate of 44.4%. In cycle I, the score increased to 77 with 72.2% completeness, and in cycle II it increased significantly to 89 with 83.3% completeness. The specific purpose of this study was to measure the effectiveness of Kahoot interactive media in improving understanding of the concept of fractional summation, increasing student active participation, and creating a more enjoyable and meaningful learning atmosphere. It is hoped that the results of this research can encourage teachers to use similar interactive media to improve the quality of mathematics learning in the classroom.